Factors influencing prognosis for occupational hand eczema. (1st December 2019) - Olesen, C.M.; Agner, T.; Ebbehøj, N.E.; Carøe, T.K.
Summary: Hand eczema is a common skin disease causing itchy skin patches on the hands, which can have a significant impact on the quality of life of affected individuals. Occupational hand eczema is when the condition is caused or made worse by factors in the workplace. Occupational hand eczema affects up to 30% of people in 'high risk' occupations, such as jobs like hairdressing in which the hands stay wet for prolonged periods (known as wet work) or where the hands come into contact with irritants or allergens. In this study the authors, based in Copenhagen, Denmark, looked at factors influencing the prognosis (likely outcome, such as whether or not it will improve) for occupational hand eczema. By using files from the Danish Labor Market Insurance, patients with occupational hand eczema in the period January 2010 to December 2011 were identified and included in the study. Information on gender, age, occupation, wet work, atopic eczema (a common type of eczema in childhood) and contact allergy (skin allergy caused by contact with an allergen) was obtained from the files. In 2015, participants received a questionnaire about lifestyle factors, occupation and persistence of hand eczema. A total of 1491 out of 2703 patients responded to the question regarding persistence of hand eczema and were included in the study. A total of 19.3% of patients reported that their hand eczema had completely healed. Current tobacco smoking and a high level of stress were factors associated with persistence of hand eczema, while a high level of exercise was significantly related to healing of eczema. Change of profession was a favorable prognostic factor (meaning it led to improvement), while age, gender, atopic eczema, contact allergy and education did not significantly influence the prognosis. The study showed that traditionally important risk factors such as atopic eczema and contact allergy had no marked influence on prognosis, while lifestyle factors were of major importance. The findings indicate that risk factors may vary over time, allowing for new perspectives on prevention, with increased focus on lifestyle factors.